A PROBING ON FOOD PROCESSING INDUSTRY TO IMPROVE RURAL INCOME IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
A well-developed food processing industry is expected to increase agricultural prices, reduce waste, secure added value, promote crop diversification, create employment opportunities, and generate export income. Growth in the food processing industry will lead to an increase in demand for agricultural products, vegetables, fruits, etc., leading to an increase in agricultural income. The food industry is closely tied to the rural economy, as all raw materials are produced by rural people. Therefore, the growth of the food industry, whether positive or negative, will have a direct impact on India's rural economy. The food processing industry helps reduce inequalities between rural and urban areas and ensures household food and nutritional security at an affordable price for all. The development of agro-based industries is easy to establish and has the potential to provide stable additional income to rural populations without large initial investments. Therefore, the development of the agricultural industry plays an important role in the process of economic development of the country as a whole. We have attempted to review the literature related to the study of the food processing industry in India and other countries. For the healthy development of the food industry, various government committees, experts, researchers, agricultural universities, universities, and research institutions have published reports and results after studying the problems and various aspects of the food industry. is being announced. We contributed by making recommendations.